Assessment of the technological dimension in the industrial and development policies in Malaysia / Mohammad Ikmal Kadir Mohd Arshad - Mohammad Ikmal Kadir , Mohd Arshad (2023)
This research examined the impact of Malaysia's Industrial Policies on technological advancement and economic growth within the context of the country's heavy dependence on industrialisation, particularly its manufacturing sector. The study aimed to address the lack of coordination and continuity in policy implementation, which led to overlapping initiatives and hindered the effective realisation of technological advancements. The research problem revolved around the challenges posed by disjointed policy plans and the subsequent impact on the advancement of technological capabilities. Through an in-depth qualitative approach, the study analysed Malaysia's industrial policies from 2006 to 2020, encompassing key plans like the Third Industrial Masterplan, Ninth Malaysia Plan, Tenth Malaysia Plan, Eleventh Malaysia Plan, and National Key Economic Areas. The research methodology involved reviewing relevant literature, comparative analysis of policies, and the development of an assessment framework focusing on technological dimensions. The analysis revealed that while the policies consistently emphasised human capital development, there were variations in execution strategies. Despite the focus on technological advancement, the productivity growth of Malaysia's economy remained inconsistent. The manufacturing sector, especially the Electrical and Electronics (E&E) industry, faced challenges with a high demand for low-skilled labour, contrary to the goal of fostering high-skilled technology-savvy employment. The lack of coordination between policy plans hindered private sector involvement in technological development. The policies often initiated programs without proper alignment with previous plans, leading to a lack of clear strategies for empowering the private industry. This lack of continuity impacted the transition to higher technological capabilities within industries, raising doubts about the effectiveness of policies intended to involve the private sector in technological advancements. The study also found that overlapping policies resulted in redundant resource allocation and hindered the growth of crucial sectors like E&E. This lack of coordination contributed to inconsistent contributions to GDP from technology-focused sectors. For example, the contribution of telecommunication services significantly declined despite the emphasis on private sector industries during the tenth Malaysia plan. To address these issues, the study recommended a comprehensive assessment of the technological dimensions of industrial policies. It highlighted the importance of aligning policies and overcoming overlapping initiatives to effectively promote technological advancement and sectoral growth. The research underscored the necessity of addressing challenges related to private sector empowerment and policy coordination. Overall, this research shed light on the complexities of Malaysia's industrial policies and their impact on technological advancement and economic growth. By identifying issues related to coordination, alignment, and private sector involvement, the study provided insights that can contribute to more effective policy formulation and implementation in the future.